A COMBINATION BETWEEN RELAXATION AND MASSAGE TEQHNIQUES FOR MOTHERS TO RELIEVE PAIN INTENSITY, DURATION OF LABOR AND APGAR SCORES FOR NEWBORN - Ni Putu Karunia Ekayani (poltekkes kemenkes mataram, 2017)
a labor pain can affect maternal conditions for instance fatigue, fear, anxiety or worry and cause stress that may cause the interference on uterus contractions and influence the length of labor. One of nonpharmacologic methods that can be used to relievea labor pain is a breathing relaxation and massage techniques. The research aimed to analyze the influence of combination between breathing relaxations and massage techniques for mothers against pain intensity, duration of labor and APGAR scores for newborn at the Public Health Center of Masbagik East Lombok. This research used Quasi-Experimental with pretest-posttest control group design. The sample applied 30 mothers who were in the first stage of labor that meet the inclusion criteria. The data were analyzed by Wilcoxon Sign-Rank Test, Mann-Whitney test and t two independent samples. The result indicated the comparison of pain intensity in the the pretest and posttest of control group was p = 0.051>0.05 which means there is no difference on pain intensity before and after treatment in the control group. Although the comparison of pain intensity on the group that received the combination techniques is obtained either pretest or posttest was p=0.001<0.05 which means there is a difference which signed by the reduction of pain intensity before and after the treatment by 2.93. Besides, there was a correlation between the implementation of the technique against duration of labor by cervical opening as indicator (p = 0.000). APGAR scores on newborn on the group that received the technique of relaxation and massage was 7-10 (normal). In short, the implementation of the technique can be used as an integral part of providing basic help for mothers to relieve labor pain and to accelerate delivery process.